Advances in the use of local anesthetic extended-release systems in pain management - Yulu Chen; Jingmei Xu; Ping Li; Liyang Shi; Sha Zhang; Qulian Guo; Yong Yang (Taylor & Francis Group, 2024)
AbstractPain management remains among the most common and largely unmet clinical problems today. Local anesthetics play an indispensable role in pain management. The main limitation of traditional local anesthetics is the limited duration of a single injection. To address this problem, catheters are often placed or combined with other drugs in clinical practice to increase the time that local anesthetics act. However, this method does not meet the needs of clinical analgesics. Therefore, many researchers have worked to develop local anesthetic extended-release types that can be administered in a single dose. In recent years, drug extended-release systems have emerged dramatically due to their long duration and efficacy, providing more possibilities for the application of local anesthetics. This paper summarizes the types of local anesthetic drug delivery systems and their clinical applications, discusses them in the context of relevant studies on local anesthetics, and provides a summary and outlook on the development of local anesthetic extended-release agents.